Inhibition of nitrifying bacteria from heterocyclic N-containing organic compounds from municipal sludge hydrothermal liquefaction - Romero, Adrian D.; Poli, João V.; Larson, Sean; Stagg-Williams, Susan; Carter, Ray; Sturm, Belinda S. M. (Frontiers in Chemical Engineering, 2025)
Hydrothermal liquefaction (HTL) is a thermochemical technology that converts wet biomass into biochar and biocrude at high temperatures and pressures. HTL can be utilized within municipal wastewater treatment to convert waste activated sludge (WAS) into valuable resources, but HTL by-products include an aqueous coproduct (ACP) that has been characterized for its biological toxicity, high ammonia, and presence of heterocyclic N-containing organic compounds (HNOCs). This study evaluated the inhibitory effects of the most prevalent HNOCs on autotrophic nitrifiers present in WAS, by determining the concentration that reduces ammonia uptake by 50 percent (IC50). 2-pyrrolidinone, pyrazine, and 2- piperidinone and their derivatives were the most prevalent HNOCs in ACP from WAS at concentrations of 8.98, 6.05, and 0.40 mM respectively. The IC50 of 2-pyrrolidinone and pyrazine were 5.2 × 10−5 and 2.0 × 10−3 mM, respectively. The IC50 of the ACP was 0.08% (%v/v). This corresponded to concentrations of 2- pyrrolidinone, pyrazine, and 2-piperidinone of 7.52 × 10−3, 5.07 × 10−3, and 3.36 × 10−4 mM, respectively. The impact of ACP storage was also tested. ACP stored for 15 weeks exhibited less inhibitory effects on the nitrifying community compared to ACP stored for 1 week. The % maximum ammonia uptake rate was reduced by 23% for the 15-week stored ACP, in contrast to 51% reduction for ACP stored for 1 week. Results of this study provide guidance for how ACP recycle can be incorporated at a wastewater treatment plant without inhibiting nitrification, enhancing the feasibility of using HTL as a solids processing technology.